The Effect of Applying Rigid Taping to Quadriceps Muscles on Knee Extension Strength and Jumping Distance - Yasar, Burak Yasin (Orthop J Sports Med, 2014)
OBJECTIVES: The scientific literature is insufficient to support the use of elastic or rigid taping for the prevention or treatment of musculoskeletal injury or performance enhancement. The aim of this study was to analyze the effects of applying rigid taping on the knee extension strength and lower limb function in healthy subjects. METHODS: Twenty eight healthy volunteers (age: 20.9 ± 1.1 years) were randomly assigned to two groups of 14 subjects each: Placebo/sham tape and rigid tape (Rigid tape application over the same muscles). All individuals were assessed for single and double leg hops and peak isometric and concentric isokinetic torque before and after interventions. RESULTS: There were no statistically significant differences in jumping distances, isometric peak torque, isokinetic peak torque and total work done between groups. CONCLUSION: Application of rigid tape to quadriceps muscles did not significantly change lower limb functions, jump distance and knee extensor peak torque in healthy sedentary subjects.